Trends and Directions of Research on Innovation in Islamic Education: A Bibliometric Analysis - Rizki, Aulia; Jannah, Miftahul; Abdi, Dira (Published by Center for Research and Community Service (LP2M) in cooperation with the Postgraduate Program of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2025)
This study aims to analyze the trends and directions of research on innovation in Islamic education using a bibliometric approach based on publications indexed in the Web of Science (WoS) from 2006 to mid-2025. The methods employed include citation analysis, collaborative network analysis, and keyword mapping using VOSviewer software. The results show a significant increase in the number of publications and citations since 2012, with a peak in 2018 and the highest citation surge occurring in 2024. Al-Jami'ah: Journal of Islamic Studies, the author Abdullah, and an article focusing on Islamic higher education in Indonesia emerged as the most influential. In addition, Universitas Islam Negeri Sunan Kalijaga Yogyakarta was identified as the most cited institution. In terms of collaboration, strong national author networks were identified, although international collaboration remains limited. Keyword analysis revealed the dominance of the theme “Islamic education” and its connection to contemporary issues such as sustainability, environment, and 21st-century competencies. The study concludes that although innovation in Islamic education is gaining increasing global attention, there remains significant potential to strengthen cross-national and interdisciplinary collaboration to enhance the future impact and relevance of the field.